Dracula - Stoker, Bram; Fawzy, Fatma ElZahraa; Kosary, Mohamed (Giza Dar Al- Farouk for cultural investments, 2023)
Originally published in 1897, "Dracula" is an epistolary work ; composed of different sorts of texts like letters and journal entries, written by a multitude of characters. The novel begins with "Jonathan Harker", a real estate worker, who travels from his home in London to the distant land of Transylvania to meet with "Count Dracula", a client who wants to purchase a house in London.The novel belongs to Gothic literature which uses terror as a plot device within a mystical setting or with supernatural elements at play to comment on social, political, and religious tensions (and anxieties) of a certain time period or community ; even if this is done subtly. There is also usually a romance or romantic element involved
Keywords: English Literature; English Stories